2021
DOI: 10.3390/jpm11121355
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Association between Waist-to-Hip Ratio and All-Cause Mortality in Stage 3–5 Chronic Kidney Disease Patients with Body Mass Index Paradox

Abstract: The obesity paradox, referring to the association of high body mass index (BMI) with low all-cause mortality risk, is found in patients with chronic kidney disease (CKD). Central obesity is associated with metabolic syndrome and may have better prognostic value than BMI for all-cause mortality. Whether central obesity is associated with all-cause mortality in cases of obesity paradox in CKD patients remains unknown. We included 3262 patients with stage 3–5 CKD, grouped into five quintiles (Q1–5) by waist-to-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In a chronic renal insufficiency cohort study, inflammation markers (IL-1β, IL-1 receptor antagonist, IL-6, TNF-α, hs-CRP, and fibrinogen) were associated with decreased kidney function [ 30 ]. We reported a reversed J-shaped association of odds ratios for malnutrition–inflammation according to the BMI of patients with CKD stages 3–5 in our previous study [ 22 ]. In patients with CKD stages 4 and 5 with a high BMI, malnutrition–inflammation was significantly decreased compared with that of patients with a low BMI, resulting in a protective effect on renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a chronic renal insufficiency cohort study, inflammation markers (IL-1β, IL-1 receptor antagonist, IL-6, TNF-α, hs-CRP, and fibrinogen) were associated with decreased kidney function [ 30 ]. We reported a reversed J-shaped association of odds ratios for malnutrition–inflammation according to the BMI of patients with CKD stages 3–5 in our previous study [ 22 ]. In patients with CKD stages 4 and 5 with a high BMI, malnutrition–inflammation was significantly decreased compared with that of patients with a low BMI, resulting in a protective effect on renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Postorino et al [ 39 ] and Kim et al [ 40 ] revealed increased all-cause mortality with increasing central obesity in the ESRD population, and Elsayed et al [ 45 ] and Kramer et al [ 46 ] noted increased cardiac events and mortality as central obesity increased in advanced CKD populations. Our previous study identified a reverse J-shaped association between BMI and all-cause mortality [ 8 ] and U-shaped association between central obesity and all-cause mortality [ 22 ] in the advanced CKD population. The present study revealed that a low BMI was associated with relatively high mortality, and a high BMI was associated with relatively low mortality in patients with CKD stages 1–3 and 4/5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously [ 25 ], two affiliated hospitals of Kaohsiung Medical University in southern Taiwan, participated in the Kaohsiung CKD Delayed Dialysis Comprehensive Care Program Study from 11 November 2002 to 31 May 2009, and followed up until 31 December 2014. Patients with CKD stages 1–5 who did not receive renal replacement therapy were included as inclusion criteria (N = 3659) at first, and (1) acute kidney injury, defined as >50% decrease in estimated glomerular filtration rate (eGFR) within 3 months (N = 62), (2) lost to follow-up in less than 3 months (N = 90), (3) chronic kidney disease stage 5 (N = 1007), was excluded, then finally this analysis included 2500 patients with CKD stages 1–4 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These patients were participating in the Integrated CKD Care Program Kaohsiung for Delaying Dialysis. The study was conducted from 11 November 2002 to 31 May 2009, with follow-ups occurring until 31 December 2014, as previously described [ 22 ]. We included patients with stage 1–5 CKD whose estimated glomerular filtration rate (eGFR) was calculated by the Modification of Diet in Renal Disease (MDRD) formula.…”
Section: Methodsmentioning
confidence: 99%